x(2-x)(2+x)=2+x

Simple and best practice solution for x(2-x)(2+x)=2+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(2-x)(2+x)=2+x equation:


Simplifying
x(2 + -1x)(2 + x) = 2 + x

Multiply (2 + -1x) * (2 + x)
x(2(2 + x) + -1x * (2 + x)) = 2 + x
x((2 * 2 + x * 2) + -1x * (2 + x)) = 2 + x
x((4 + 2x) + -1x * (2 + x)) = 2 + x
x(4 + 2x + (2 * -1x + x * -1x)) = 2 + x
x(4 + 2x + (-2x + -1x2)) = 2 + x

Combine like terms: 2x + -2x = 0
x(4 + 0 + -1x2) = 2 + x
x(4 + -1x2) = 2 + x
(4 * x + -1x2 * x) = 2 + x
(4x + -1x3) = 2 + x

Solving
4x + -1x3 = 2 + x

Solving for variable 'x'.

Reorder the terms:
-2 + 4x + -1x + -1x3 = 2 + x + -2 + -1x

Combine like terms: 4x + -1x = 3x
-2 + 3x + -1x3 = 2 + x + -2 + -1x

Reorder the terms:
-2 + 3x + -1x3 = 2 + -2 + x + -1x

Combine like terms: 2 + -2 = 0
-2 + 3x + -1x3 = 0 + x + -1x
-2 + 3x + -1x3 = x + -1x

Combine like terms: x + -1x = 0
-2 + 3x + -1x3 = 0

The solution to this equation could not be determined.

See similar equations:

| 7=43x+2x^2 | | 6x+3=4x+5 | | 4-2(x-6)=3x+56 | | -55=8x-7 | | x^6-12x^5+36x^4=0 | | 4(x+5)-6=34 | | x^2-18.5=0 | | 112/16+7z/8=5/16 | | (3x-36)+(2x+26)=90 | | 2x*2x=10 | | 114-5x=22x+21 | | v*v=W+V | | 5x-0+150=180 | | 6x-4(x-2)=7x(3x-4)+19 | | x^2-12x+77=0 | | 6x+6(2x-5)=-10-2x | | 3x^2-16x+12=0 | | 3y=180 | | (x+40)+(3x-10)=180 | | P+q-p-3q+5= | | 10-7x=106-28x | | 5+7x=11+7x | | 20+5=24 | | 2x-36=100 | | 3(x+3)=(3x+9) | | 30=-11x | | (2x-3)(2x-3)=0 | | 5x-y+150=180 | | -N+(v*b*b)=r | | (x-2)(x+2)=(x-1) | | 2.6z^2-0.9z+2=0 | | m-1=2 |

Equations solver categories